2005
DOI: 10.3182/20050703-6-cz-1902.01905
|View full text |Cite
|
Sign up to set email alerts
|

Slip-Deceleration Control in Anti-Lock Braking Systems

Abstract: Abstract. In road vehicles, wheel locking can be prevented by means of closedloop Anti-lock Braking Systems (ABS). Two output measured variables are usually considered for regulation: wheel-deceleration and wheel longitudinal slip. The traditional controlled variable used in ABS is the wheel deceleration, since it can be easily measured with a simple wheel encoder; however, it can be dynamically critical if the road-surface rapidly changes. On the other hand, the regulation of the longitudinal slip is much rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…On the other hand, assuming robust estimation of longitudinal wheel slip, the wheel slip control is simpler from a dynamical point of view and has the feature that the applied torque converges to a fixed value. Hence, the controlled system shows lesser oscillations compared to wheel-acceleration control designs [17], [18]. The controller, however, is highly sensitive to set-point selection.…”
Section: Survey Of Control Strategies For Wheel Slip Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, assuming robust estimation of longitudinal wheel slip, the wheel slip control is simpler from a dynamical point of view and has the feature that the applied torque converges to a fixed value. Hence, the controlled system shows lesser oscillations compared to wheel-acceleration control designs [17], [18]. The controller, however, is highly sensitive to set-point selection.…”
Section: Survey Of Control Strategies For Wheel Slip Controlmentioning
confidence: 99%
“…Lastly, a mixed slip-deceleration control was introduced in [18]. The basic idea of this control approach is to select the regulated variable as a convex combination of the wheel slip and wheel deceleration.…”
Section: Proportional Integral Derivative (Pid) Controllersmentioning
confidence: 99%
“…Minimization of the braking distance is obtained by maximizing the friction force. Generally, this force is incorporated into the control law by considering the longitudinal vehicle dynamics (Drakunov et al, 1995;Alvarez et al, 2000;El Hadri et al, 2001;Petersen et al, 2001;Anwar and Ashrafi, 2002;Savaresi et al, 2005):…”
Section: Maximization Of the Braking Effect On The Vehiclementioning
confidence: 99%
“…The techniques studied nowadays include sliding mode control (Drakunov et al, 1995;El Hadri et al, 2001), fuzzy logic (Yonggon and Stanislaw, 2002), optimal control (Petersen et al, 2001), and predictive strategy (Anwar and Ashrafi, 2002). Traditionally, the control variables are either the wheel angular deceleration or the wheel slip but Savaresi et al (2005) has recently suggested a combination of the two. Nevertheless, the main difficulty for the design of a brake controller is that the set point producing the maximum friction force is unknown and subject to variations.…”
Section: Introductionmentioning
confidence: 99%
“…Drakunov, Ozguner, Dix and Ashrafi 1995;Buckholtz 2002;Johansen, Petersen, Kalkkuhl and Lu¨demann 2003;Tanelli, Astolfi and Savaresi 2006a, b;Savaresi, Tanelli and Cantoni 2007). In the field of automatic braking control many different approaches have been proposed, ranging from classical regulation loops based on linearised models, to sliding mode, fuzzy-neural or hybrid control strategies (Drakunov et al 1995;Johansen, Petersen, Kalkkuhl and Lu¨demann 2001;Buckholtz 2002;Lin and Hsu 2002;Savaresi et al 2005). Even if these advanced control techniques are indeed very powerful, most industrial ABS are still based on hydraulic braking systems which do not, in general, allow to achieve continuous modulation of the braking torque.…”
Section: Introductionmentioning
confidence: 99%